Microvertebrate studies in archaeological contexts: Middle Paleolithic to early Holocene past environments - López-García, Juan Manuel (2022)
Since 2016, the Microvertebrate Working Group (MVWG), which is part of the International Council for Archaeozoology (ICAZ), has held meetings every 2 years with the aim of exchanging data from the study of herpetofauna and small mammals in archaeological contexts. This special issue is the culmination of the III Microvertebrate Working Group (MVWG) meeting that was held virtually between September 1st and 2nd 2020 at the Institut de Paleoecologia Humana i Evolució Social (IPHES), Tarragona, Spain. The meeting gathered 50 small vertebrate zooarchaeologists virtually from Algeria, Argentina, Chile, France, Germany, Italy, Norway, the Philippines, Scotland, Serbia, Spain, Switzerland, and Tunisia. The present special issue is the result of a total of 18 oral communications and 11 posters.